Investigation of the Tensile Strength of Sea Sand Concrete Against the Compressive Strength of the Plan - Adnan Adnan; V Safitri (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
The availability of sea sand on the beach of Ujung Tape Pinrang is in very large quantities that can be used as materials in making concrete. The purpose of the study is to analyze the characteristics of beach sand, compressive strength and tensile strength produced. An experimental research method in the Civil Engineering Laboratory, University of Muhammadiyah Parepare with a treatment system for ordinary water immersion and analysis of the characteristics of concrete mechanical properties using a compression machine test. The results of the study at the maintenance age of 28 days with a planned compressive strength of 20 MPa produced a compressive strength of 28.29 MPa and a tensile strength of 7.78 MPa, a planned compressive strength of 24 MPa resulted in a compressive strength of 29.98 MPa and a tensile strength of 8.22 MPa, and a planned compressive strength of 28 MPa produces a compressive strength of 31.40 MPa and a tensile strength of 8.44 MPa. The results of the study on compressive strength and tensile strength showed an increase in each increase in planned compressive strength.